Psychological Manifestations of Celiac Disease Autoimmunity in Young Children - Smith, Laura B; Lynch, Kristian F; Kurppa, Kalle; Koletzko, Sibylle; Krischer, Jeffrey; Liu, Edwin; Johnson, Suzanne Bennett; Agardh, Daniel (Pediatrics (Evanston), 2017)
Psychological symptoms can be associated with celiac disease; however, this association has not been studied prospectively in a pediatric cohort. We examined mother report of psychological functioning in children persistently positive for tissue transglutaminase autoantibodies (tTGA), defined as celiac disease autoimmunity (CDA), compared with children without CDA in a screening population of genetically at-risk children. We also investigated differences in psychological symptoms based on mothers' awareness of their child's CDA status. The Environmental Determinants of Diabetes in the Young study followed 8676 children to identify triggers of type 1 diabetes and celiac disease. Children were tested for tTGA beginning at 2 years of age. The Achenbach Child Behavior Checklist assessed child psychological functioning at 3.5 and 4.5 years of age. At 3.5 years, 66 mothers unaware their child had CDA reported more child anxiety and depression, aggressive behavior, and sleep problems than 3651 mothers of children without CDA (all s ≤ .03). Unaware-CDA mothers also reported more child anxiety and depression, withdrawn behavior, aggressive behavior, and sleep problems than 440 mothers aware of their child's CDA status (all s ≤.04). At 4.5 years, there were no differences. In 3.5-year-old children, CDA is associated with increased reports of child depression and anxiety, aggressive behavior, and sleep problems when mothers are unaware of their child's CDA status. Mothers' knowledge of their child's CDA status is associated with fewer reports of psychological symptoms, suggesting that awareness of the child's tTGA test results affects reporting of symptoms.